SENSORY MARKETING AND ITS ROLE IN ENHANCING MARKETING PERFORMANCE: “AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS IN FOUR- AND FIVE-STAR RESTAURANTS IN THE CITY OF DOHUK” - Salim, Refink; Rashid, Mevan; Salih, Sami (Humanities Journal of University of Zakho, 2024)
The current paper aims to study sensory marketing and its role in enhancing marketing performance in four- and five-star restaurants in the city of Dohuk. Sensory marketing is one of the approaches that can help organizations increase their profitability and enhance their marketing performance, as the customer is often attracted to the brand on the basis of his sensory experience. The researchers used the descriptive analytical method, and a questionnaire was administered to survey the opinions of the research sample, i.e., 71 workers from four- and five-star restaurants in the city of Dohuk. By using statistical methods, the results were analyzed and the hypotheses were tested. The most important points of conclusion indicate that sensory marketing has a significant effect on enhancing marketing performance, and the largest significant effect on the level of dimensions was for the sensory promotion dimension, compared to the least significant effect of the sensory pricing dimension on marketing performance. Finally, it was recommended to develop pricing policies that take into account the difference in income levels of customers and to target the emotional and cognitive side of customers through the use of lighting, colors, music, and attention-grabbing designs and shapes.